Cyber-Attack on Overloading Multiple Lines: A Bilevel Mixed-Integer Linear Programming Model - Tan, Yi; Li, Yong; Cao, Yijia; Shahidehpour, Mohammad (IEEE transactions on smart grid, 2018)
In this letter, we propose a bilevel mixed-integer linear programming (BMILP) model for cyber-attack on multiple transmission lines in economic dispatch by injecting false load data. In contrast to the state of art research, the proposed model is able to overload a set of lines that are selected by the attacker in the framework of BMILP. Therefore, the proposed model is computationally efficient due to its bilevel linear programming property. The effectiveness of the proposed bilevel linear approach has been successfully validated on an IEEE 118-bus system.